Le visage comme tableau - Coulombe, Maxime (Ciel variable)

(untitled) (Les Productions Ciel variable, 2007)
The author argues that in order to fully understand Orlan's Self-Hybridations series, one must return to her highly controversial series of performances, The Reincarnation of Sainte-Orlan. In this earlier series, the artist physically transformed her body to distance herself from recognized canons of beauty, in order to make her body resemble what she felt was her true interior identity. In Self-Hybridations, the digital combination of her face with pre-Columbian masks virtually builds on this concept. By sidestepping contemporary aesthetic norms, she suggests a novel conception of beauty and identity, one that is fully freed from the constraints of the physical body.